Crescent dawn - Cussler, Clive (London M. Joseph, 2011)
In AD 327, a Roman galley with an extraordinary cargo barely escapes a pirate attack. In 1916, a British warship mysteriously explodes in the North Sea. In the present day, a cluster of important
1
Keywords: Marine biologists -- Fiction